CTN 328: immunogenicity outcomes in people living with HIV in Canada following vaccination for COVID-19 (HIV-COV): protocol for an observational cohort study - Cecilia T Costiniuk; Jean-Pierre Routy; Shari Margolese; Enrico Mandarino; Joel Singer; Mohammad-Ali Jenabian; Mario Ostrowski; Jonathan B Angel; Ann Burchell; Darrell Tan; Colin Kovacs; Mark Hull; et al. (BMJ Open)
Introduction Most existing vaccines require higher or additional doses or adjuvants to provide similar protection for people living with HIV (PLWH) compared with HIV-uninfected individuals. Additional research is necessary to inform COVID-19 vaccine use in PLWH.Methods and analysis This multicentred observational Canadian cohort study will enrol 400 PLWH aged >16 years from Montreal, Ottawa, Toronto and Vancouver. Subpopulations of PLWH of interest will include individuals: (1) >55 years of age; (2) with CD4 counts <350 cells/mm3; (3) with multimorbidity (>2 comorbidities) and (4) ‘stable’ or ‘reference’ PLWH (CD4 T cells >350 cells/mm3, suppressed viral load for >6 months and <1 comorbidity). Data for 1000 HIV-negative controls will be obtained via a parallel cohort study (Stop the Spread Ottawa), using similar time points and methods. Participants receiving >1 COVID-19 vaccine will attend five visits: prevaccination; 1 month following the first vaccine dose; and at 3, 6 and 12 months following the second vaccine dose. The primary end point will be the percentage of PLWH with COVID-19-specific antibodies at 6 months following the second vaccine dose. Humoral and cell-mediated immune responses, and the interplay between T cell phenotypes and inflammatory markers, will be described. Regression techniques will be used to compare COVID-19-specific immune responses to determine whether there are differences between the ‘unstable’ PLWH group (CD4 <350 cells/mm3), the stable PLWH cohort and the HIV-negative controls, adjusting for factors believed to be associated with immune response. Unadjusted analyses will reveal whether there are differences in driving factors associated with group membership.Ethics and dissemination Research ethics boards at all participating institutions have granted ethics approval for this study. Written informed consent will be obtained from all study participants prior to enrolment. The findings will inform the design of future COVID-19 clinical trials, dosing strategies aimed to improve immune responses and guideline development for PLWH.Trial registration number NCT04894448.